2002
DOI: 10.1902/jop.2002.73.6.664
|View full text |Cite
|
Sign up to set email alerts
|

Oral Manifestations of Acute Myelomonocytic Leukemia: A Case Report and Review of the Classification of Leukemias

Abstract: Oral health care professionals, especially periodontists, must recognize that gingival enlargement may represent an initial manifestation of an underlying systemic disease. Acute myelogenous leukemia is a hematological disorder with a predilection for gingival involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 20 publications
0
34
0
3
Order By: Relevance
“…The resulting decrease of functional white blood cells, red blood cells and platelets is responsible for immunodeficiency, anaemia, and thrombocytopenia, respectively. [1][2][3][4] The leukaemias are subdivided into chronic and acute forms. Chronic leukaemias involve relatively well-differentiated leukocytes, presenting a slow onset and run an indolent course.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting decrease of functional white blood cells, red blood cells and platelets is responsible for immunodeficiency, anaemia, and thrombocytopenia, respectively. [1][2][3][4] The leukaemias are subdivided into chronic and acute forms. Chronic leukaemias involve relatively well-differentiated leukocytes, presenting a slow onset and run an indolent course.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][20][21][22] While there is no consensus in the literature about the most prevalent oral manifestations in leukemic patients, gingival bleeding, gingival swelling, ulcers and petechiae are the most frequently reported. 1,4,5,[8][9][10][11][12]16,17,19 In patients undergoing active treatment for leukemia, gingival bleeding and petechiae were the most common findings in the oral cavity, occurring twice as often in patients having the acute form of leukemia. 13 Hou et al, 18 in a retrospective study of patients at diagnosis, found that gingival bleeding was the second earliest sign of disease.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, thrombocytopenia is considered an important secondary effect of the disease and a potential risk factor. [3][4][5] Oral manifestations (gingival swelling [7][8][9][10][11][12] and gingival and oral bleeding [13][14][15][16][17][18] ) have been associated with leukemia. Gingival swelling is the most common oral sign in untreated patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…L'âge médian de survenue est de 64 ans [7], elle est plus fréquemment observée chez l'homme que chez la femme [5]. La chimiothérapie antimitotique [10], la radiothérapie externe [15] ou l'exposition au benzène [3] représentent des facteurs de risques qui peuvent orienter la démarche diagnostique. Le taux de survie est très variable (de 20 à 60 %) : il dépend du caryotype et de la possibilité de trouver un donneur HLA compatible pour effectuer une allogreffe.…”
unclassified